Pre-Marital Education From an Al-Quran Perspective - Widyastuti, Dwi; Hardianti, Pani Siti (CV. Publikasi Indonesia, 2025)
Premarital education is an important step in preparing individuals to build a household that is sakinah, mawaddah, and rahmah. The Qur'anic perspective provides a strong normative foundation regarding the importance of spiritual, moral, psychological, and social readiness before entering marriage. This study aims to analyze the concept of premarital education in the perspective of the Qur'an and its relevance to the needs of modern Muslim couples. The research method used is a qualitative literature study with thematic interpretation analysis of Qur'anic verses related to marriage. The results of the study show that premarital education in the Qur'an includes the development of faith, morals, emotional maturity, understanding of the rights and obligations of the spouse, and household management skills. The implementation of premarital education based on the Qur'an is expected to be able to reduce the divorce rate and form a harmonious family.